Design and experimental study of turning tools with linear cutting edges and comparison to commercial tools. Issue 9 (August 2016) - Monka, Peter; Monkova, Katarina; Balara, Milan; Hloch, Sergej; Rehor, Jan; Andrej, Andrej; Somsak, Matej
Abstract In the article, a design and experimental study of the non-traditional turning tool is carried out and compared to commercial tools. The quality and the efficiency of the machining process is considerably affected by the cutting tools, there being a tendency to look for new non-traditional tools and their geometry. One such tool is a tool with a linear cutting edge. Research into its application towards machining capabilities and its comparison to the classical, mass produced, tools was the goal of this investigation. For this reason, the tools were designed at FMT TU Kosice with the seat in Presov to find new solutions to preserve the tool's advantages and eliminate its disadvantages. After tool designing, various types of experiments were carried out, dealing with the roughness of machined surface and the turning force. The shapes of the chips and life time of the tools were investigated together with the technological aspects (i.e. feed and speed). Regression analysis and the finitary method of matrix inversion were selected as the methods to interpret the experimental results. The results show that a tool with a linear cutting edge achieves lower values of the surface profile parameterRz at higher feeds, compared to a commercial tool, which is especially designed to finish the turning operations. On the other hand, from the point of view of energy consumption, the selected commercial tool is more effective. These findings will enable the producer to make a better decision on which type of tool should be used for machining in specific conditions to achieve the best machined surface quality at the required level of energy consumption.